2006
DOI: 10.1590/s0080-62342006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimentos e práticas de trabalhadoras de creches universitárias relativos às infecções respiratórias agudas na infância

Abstract: RESUMODada a elevada freqüência de infecções respiratórias agudas em creches, o objetivo deste trabalho foi identificar conhecimentos e práticas de trabalhadoras de creches relativos à prevenção, detecção precoce e manejo desses agravos. Mediante quatorze entrevistas estruturadas em duas creches universitárias da cidade de São Paulo, verificou-se que as trabalhadoras: demonstram familiaridade com diversos agravos; apontam febre e respiração ruidosa como sinais de gravidade; consideram poluição e transmissão co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
1
7
0
5
Order By: Relevance
“…It is known that the interaction with social networks and their incorporation into health practices are a challenge to health professionals, because there is still the difficulty of overcoming the illusion that scientific knowledge is unique (9) . respondents, this study corroborates the findings of research carried out in São Paulo, which revealed the need for educators to take part in ongoing updates on the health of children through meetings with health professionals to discuss the relevant issues (3) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is known that the interaction with social networks and their incorporation into health practices are a challenge to health professionals, because there is still the difficulty of overcoming the illusion that scientific knowledge is unique (9) . respondents, this study corroborates the findings of research carried out in São Paulo, which revealed the need for educators to take part in ongoing updates on the health of children through meetings with health professionals to discuss the relevant issues (3) .…”
Section: Discussionsupporting
confidence: 88%
“…The supply of instrumentalization for early childhood professionals enables them to develop the ability to recognize early signs and symptoms indicative of situations that require specific care of professionals in Health (3) , with positive impacts on the effectiveness of preventive actions.…”
Section: Introductionmentioning
confidence: 99%
“…É necessário o desenvolvimento de atividades de atualização/capacitação para educadores, incluindo promoção da saúde infantil com manejos adequados aos agravos desta fase do crescimento humano (5) . No entanto, a falta de comunicação entre os professores e pais/responsáveis é um dos principais obstáculos encontrados para a resolutividade da pediculose no âmbito escolar, além das práticas apropriadas de enfrentamento limitadas (6) .…”
Section: Introductionunclassified
“…Nesta, realizei um estudo em uma creche universitária da cidade de São Paulo, intitulado "Conhecimentos e práticas de trabalhadoras de creches universitárias relativos às infecções respiratórias na infância" (Alves, 2006). A opção por estudar as Infecções Respiratórias Agudas (IRA) deu-se pela magnitude desses agravos na nossa população infantil.…”
Section: Apresentação Do Trabalhounclassified
“…Nessa nova ótica, a creche estaria sendo complementar à família e à mãe, e não as substituindo, o que serviria como apoio para melhorar as relações familiares, aproximaria a família da comunidade e libertaria a mulher da rotina da vida doméstica (Merisse, 1997 natural das mulheres (Veríssimo, Fonseca, 2003). Muitos dos cuidados prestados em instituições de educação infantil são baseados no senso comum (Maranhão, 1998;Alves, Veríssimo, 2006;Martins, Veríssimo, 2006), pois, na maioria das creches no Brasil, até recentemente, houve pouco investimento na formação e capacitação de seus trabalhadores (Avancini, 2000), o que inviabiliza o cuidado integral e sem riscos de iatrogenias às crianças ali atendidas.…”
Section: Introductionunclassified